Near Surface 2010 - 16th EAGE European Meeting of Environmental and Engineering Geophysics 2010
DOI: 10.3997/2214-4609.20144851
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain IP and Resistivity Sections Measured at Four Landfills with Different Contents

Abstract: SUMMARYFour IP and resistivity sections measured in four landfills with different contents but in comparable geological settings are compared. The normalized chargeability makes it possible to distinguish waste from natural geological materials and to solve ambiguities remaining when the sole direct-current resistivity is used. The amplitude on the IP response is more important on the two landfills containing large amounts of biodegradable organic matter and disseminated metals. It is weaker when these materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…A clear distinctive unit reaching 300-450 mV V −1 enhances the waste layer at about 10 m depth. These results agree with Auken et al (2011), Leroux et al (2010) or Carlson et al (2001), who report a high chargeable unit related to the waste bodies.…”
Section: Landfill Mappingsupporting
confidence: 83%
See 1 more Smart Citation
“…A clear distinctive unit reaching 300-450 mV V −1 enhances the waste layer at about 10 m depth. These results agree with Auken et al (2011), Leroux et al (2010) or Carlson et al (2001), who report a high chargeable unit related to the waste bodies.…”
Section: Landfill Mappingsupporting
confidence: 83%
“…They also show how IP can significantly improve the understanding of the engineering properties of the subsurface relative to resistivity imaging alone. Recently, , and Leroux et al (2010) have shown how the combined use of DC-TDIP could be successfully applied to landfill mapping and characterization, as it usually depicts the waste layer with a relatively high chargeable unit.…”
Section: Introductionmentioning
confidence: 99%
“…The first high‐chargeable area fits the eldest part of the waste, containing sludge and coal. This observation concurs with Leroux et al (2010) who reported a significant difference in the IP signal according to the different types of waste and the organic content in particular. The second high‐chargeable area, more in the south‐west direction, on top of metal spring deposits, also fits a high value of τ (above 2 s).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, new applications of induced polarization have emerged in environmental geophysics, including the detection and mapping of a contaminant, both at the field scale (Vanhala 1997; Kemna et al 2004; Sogade et al 2006; Flores‐Oroszco et al 2011; Flores‐Oroszco et al 2012) and at the laboratory scale (Vanhala 1992; Abdel Aal et al 2006; Cassiani et al 2009), or for the geological discrimination of clay contents (Schmutz et al 2011; Gazoty et al 2012). In the time domain, the induced polarization method has been successfully applied to landfill characterization, often displaying a chargeable unit related to the waste body (Carlson et al 2001; Johansson et al 2007; Leroux et al 2010; Gazoty et al 2012). The time‐domain field operation is simple and robust when applying standard multi‐channel acquisition systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bernstone et al (2000) showed that it was not possible to distinguish between different types of material using electrical resistivity mapping alone and that high uncertainty was present in the results. Nevertheless, a combination of electrical resistivity measurements and induced polarization (Leroux and Dahlin, 2010;Dahlin, 2012) has shown promising results, being able to distinguish between waste and geologic material. However, an advanced inversion method is required for the optimization of the results.…”
Section: Introductionmentioning
confidence: 99%